Field Ethnological Research by Scientists of the Ethnology and Local Lore Section of the Kharkiv Research Department of the History of Ukrainian Culture (1924—1929) - Стаднік, Ю. (Київський національний університет імені Тараса Шевченка, 2025)
Relevance of the research. The Soviet period in the history of Ukrainian ethnology became a challenge for the preservation of folk culture. Ukrainian folk culture was supplanted by modernisation processes, as well as Bolshevik ideology. Folklore was forgotten along with ancient crafts, trades, and customs. Researchers who observed these trends since the early 1920s had been collecting and processing cultural and artistic monuments in order to preserve them for future generations. However, the attack on scientific and cultural institutions in the late 1920s and early 1930s complicated and almost stopped this work. Therefore, an important task for today's scientists is to study the works of ethnologists of that time to accurately reproduce the development of ethnological science. A little-known but important aspect of the activities of ethnological centres in the 1920s is the specificity of their scientific and research work.The purpose of the article is to identify the key characteristics of “field” research on the material and spiritual culture of Ukraine conducted by the Ethnology and Local Lore Section of the Kharkiv Research Department of the History of Ukrainian Culture named after D. I. Bahalii in the period from December 1924 till November 1929.Conclusions. In the period from December 1924 till November 1929, the staff of the Ethnology and Local Lore Section of the Kharkiv Research Department of the History of Ukrainian Culture named after D. I. Bahalii carried out substantial efforts to collect the material and spiritual culture of Ukraine. Expedition activities facilitated academic collaboration between ethnological centres and also enhanced the scientific level of the museum institutions where the staff worked. The “field” trips of scientists helped to create a powerful source base for ethnological research with a wide geographical scope and themes, contributed to the preservation of cultural heritage that was quickly disappearing from everyday life at the time of study and today survives only partially or solely within the section’s collection.Keywords: ethnology, local history, research department, Ethnology and Local Lore Section, scientific research activities, expeditions, Kharkiv.

Актуальність. Радянський період в історії української етнології став справжнім викликом для збереження народної культури. Модернізаційні процеси, а також більшовицька ідеологія витісняли традиційну народну культуру українців. Зникали давні ремесла, промисли та народні звичаї, забувався фольклор. Дослідники, що спостерігали за цими тенденціями, вже з початку 1920-х років збирали та опрацьовували пам’ятки культури і мистецтва, щоб у такий спосіб зберегти їх для майбутніх поколінь. Однак наступ на наукові та культурні установи наприкінці 1920-х – на початку 1930-х років ускладнив та майже зупинив цю роботу. Тож важливим завданням учених сьогодення є дослідження праць етнологів того часу задля достовірного відтворення розвитку етнологічної науки. Маловідомим, але важливим аспектом діяльності етнологічних осередків 1920-х років є специфіка їхньої науково-пошукової роботи. Метою статті є визначення особливостей проведення польових досліджень матеріальної та духовної культури України на базі етнолого-краєзнавчої секції Харківської науково-дослідної кафедри історії української культури імені Д. І. Багалія у період з грудня 1924 р. по листопад 1929 р. Висновки. У період з грудня 1924 р. по листопад 1929 р. співробітниками етнолого-краєзнавчої секції Харківської науково-дослідної кафедри історії української культури імені Д. І. Багалія було здійснено вагому працю зі збору матеріальної та духовної культури України. Експедиційна діяльність сприяла науковому мережуванню етнологічних осередків, а також підвищувала науковий рівень музейних установ, у яких працювали співробітники. Польові виїзди вчених допомогли створити потужну джерельну базу для етнологічних розвідок з широкою географією та тематикою, сприяли збереженню культурної спадщини, що на час вивчення швидко виходила з ужитку, а сьогодні збереглася частково або лише в доробку секції. Ключові слова: етнологія, краєзнавство, науково-дослідна кафедра, етнолого-краєзнавча секція, науково-пошукова діяльність, експедиції, Харків.
Польові етнологічні дослідження вчених етнолого-краєзнавчої секції Харківської науково-дослідної кафедри історії української культури (1924—1929)